Comparison of temporal muscle fascia and tragal cartilage perichondrium in endoscopic type 1 tympanoplasty with limited elevation of tympanomeatal flap - Özdamar,Kadir (2020)
Abstract Introduction Elevation of tympanomeatal flap is one of the basic steps of tympanoplasty. A satisfactory level of anatomic and functional success can be achieved by using different grafts with limited tympanomeatal flap elevation. Objectives We aimed to compare the anatomic and functional success of tragal cartilage perichondrium and temporal muscle fascia in cases of endoscopic type 1 tympanoplasty performed with limited tympanomeatal flap elevation. Methods In total, 81 cases (33 females, 48 males, mean age 22.1<±<10.1 years, interval 18–49 years) which underwent transcanal endoscopic type 1 tympanoplasty with limited elevation of tympanomeatal flap were included the present study. All cases were divided into two groups as tragal cartilage perichondrium (group A) and temporal muscle fascia (group B). The comparison of the groups were made considering the pre- and postoperative air-bone gap and the tympanic membrane status. Results There was no statistically significant difference between Group A and Group B in preoperative and in postoperative air-bone gap values (p<=<0.608 and 0.529, respectively). In Group A and B, postoperative air-bone gap values demonstrated significant decrease compared to the preoperative values (p<=<0.0001). Group A and group B did not demonstrate significant differences between postoperative improvements of air-bone gap values (p<=<0.687). Graft retention success was 92.6% in group A while it was 90.0% in group B. There was no statistically significant difference between the groups in terms of graft retention success (p<=<0.166). Conclusion In accordance with the results of this study, we believe that both tragal cartilage perichondrium and temporal muscle fascia, and also in limited tympanomeatal flap elevation in endoscopic tympanoplasty are all eligible for result in safe and successful surgery.